The Influence of the Coach’s Leadership Strategy on the Motivation and Performance of Volleyball Players in the Pusri Team - Wilana, Agustinus Bintang; Rahman, Andi; Imansyah, Farizal (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study investigated the effects of different coaching leadership strategies on the motivation and performance of volleyball players in the Pusri team. By employing a mixed-methods approach, the research analyses transformational, transactional, and laissez-faire leadership styles. Results show that transformational leadership significantly enhances intrinsic motivation and performance, fostering team cohesion and individual development. Transactional leadership, while effective short-term, presents challenges in sustaining long-term motivation due to its reliance on external rewards. Laissez-faire leadership benefits self-motivated players but can negatively impact those needing more guidance. The study concludes that adaptive leadership, tailored to individual and team needs, is crucial for optimizing performance. Recommendations include prioritizing transformational techniques, balanced use of transactional methods, and selective application of laissez-faire strategies. These findings contribute to both theoretical understanding and practical applications in sports leadership.